Electro-oxidation of renewable glycerol to value added chemicals over phosphorous-doped Pt/MCNTs nanoparticles. (November 2019) - Ahmad, M S; Cheng, C K; Ong, H R; Abdullah, H; Khan, M R
Abstract: In the present work, Pt/MCNTs and P-dopedPt/MCNTs catalysts were synthesized via hydrothermal method and utilized for glycerol oxidation reaction (GOR). The catalysts were physio-chemically characterized by Brunauer-Emmett-Teller (BET), X-ray diffraction, field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) to investigate pore size, pore volume, structure and morphology of the catalysts. A remarkable reduction in BET surface area was found for P-dopedPt/MNCTs which 1.56 time less than the sole MNCTs is confirming the incorporation of phosphorous into the pore channels of Pt/MCNT. The TEM analysis of P-dopedPt/MCNTS demonstrated the uniform distribution of Pt nanoparticles over multiwalled carbon nanotubes with an average particle size of 6.23 nm. The activity and stability of the catalysts were analysed for GOR using cyclic voltammetry (CV) and chronoamperometry (CA). The CV testing showed the higher current density for P-doped Pt/MCNTs (28.33 A/m 2 ) which is 2 times higher than the Pt/MCNTs (14.20 A/m 2 ) current density. The synthesized products were analysed by high performance liquid chromatography (HPLC) analysis which demonstrated the selective synthesis of tartronic acid as a major product with maximum yield. It was found that the P-dopedPt/MCNTs have higher selectivity for tartronic acid and glyceric acid as compared to its counterpart.